Using Tasks with Some Principles of Emancipatory Education to Improve English Oral Production (2022)
ABSTRACT : This action-research aimed at fostering students’ oral production through Task Based Learning (TBL) with some principles of Emancipatory Education (EE). It was conducted in a public school in La Union Antioquia with 39 sixth graders during approximately one year. Actions developed included the implementation of the task cycle without the language focus stage. Data gathering instruments included a diagnosis, memos, voice recordings, students’ artifacts, and a questionnaire. Findings revealed students’ meaningful improvements regarding vocabulary acquisition, along with their capacity to construct well-organized complete sentences and pronunciation as well as speaking skills.